Management of Physiology Intranatal Midwifery Care for Mrs. “J” on the Gestanional Period of 39 Weeks and 6 Days with the 3rd Stage of Inpartu at Jumpandang Baru Health Center, July 31st, 2022: Manajemen Asuhan Kebidanan Intranatal Fisiologi Pada Ny”J” dengan Gestasi 39 Minggu 6 Hari Inpartu Kala III Di Puskesmas Jumpandang Makassar - Indah Lestari Sutrang; Sitti Saleha; Zelna Yuni Andryani (Jurnal Midwifery, 2023)
Introduction The third stage of labor is the uri stage, namely the birth of the baby and the release of the placenta and the amniotic membranes. Active management of the third stage is the management on the expulsion of the placenta. In most cases, the maternal morbidity and mortality in Indonesia were caused by uterine atony and retained placenta. However, these issues could actually be prevented by enhancng the active management of the third stage. Method In this research, the 7-stage of Varney management approach was employed in accordance with proper procedure based on the competence and authority of the midwifes. Result The findings of this research indicated that there were no particular obstacles found during the process of treatment given to Mrs “J” with the third stage of labor. The patient experienced a normal lower abdominal pain and pains in the perineum on day 1. However, on the next monitoring day, the patient had no complaints, and there were no complications found. Conclusion His study concluded that the research was conducted based on the mentioned approach and SOAP procedure, and it revealed that from the third stage to the fourth stage there were no obstacles and complications found in both the mother and fetus. The condition of both the mother and the baby was generally good where their vital signs were within normal limits.